Reconfigurable Braille display with phase change locking. (24th June 2016) - Soule, Cody W; Lazarus, Nathan
Abstract: Automatically updated signs and displays for sighted people are common in today's world. However, there is no cheap, low power equivalent available for the blind. This work demonstrates a reconfigurable Braille cell using the solid-to-liquid phase change of a low melting point alloy as a zero holding power locking mechanism. The device is actuated with the alloy in the liquid state, and is then allowed to solidify to lock the Braille dot in the actuated position. A low-cost manufacturing process is developed that includes molding of a rigid silicone to create pneumatic channels, and bonding of a thin membrane of a softer silicone on the surface for actuation. A plug of Field's metal (melting point 62 °C) is placed in the pneumatic channels below each Braille dot to create the final device. The device is well suited for low duty cycle operation in applications such as signs, and is able to maintain its state indefinitely without additional power input. The display requires a pneumatic pressure of only 24 kPa for actuation, and reconfiguration has been demonstrated in less than a minute and a half.